1992
DOI: 10.1007/bf00207042
|View full text |Cite
|
Sign up to set email alerts
|

Confirmation of linkage of benign familial neonatal convulsions to D20S19 and D20S20

Abstract: Benign familial neonatal convulsions (BFNC) is an idiopathic form of epilepsy beginning within the first six months of life. Its genetic origin and autosomal dominant mode of inheritance have been suspected since its first description. Recently, the BFNC gene has been localised within chromosome 20q in one large pedigree. For the first time, we confirm here (with D20S19 and D20S20) the close linkage of BFNC to chromosome 20q in six French pedigrees. In addition, the existence in these families of several cases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
24
0
2

Year Published

1994
1994
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(26 citation statements)
references
References 11 publications
0
24
0
2
Order By: Relevance
“…[14]. Another marker, D20S19, has been localized adjacent to D20S20 and D20S24 and is tightly linked to the three brain-specific phenotypes benign familial neonatal convulsions (BFNC) [15,16], low-voltage EEG (LVEEG) [17] and autosomal dominant nocturnal frontal lobe epilepsy (ADNFLE) [18]. ADNFLE is a partial epilepsy which typically begins in childhood and leads to clusters of brief seizures during light sleep or drowsing [19].…”
Section: Introductionmentioning
confidence: 99%
“…[14]. Another marker, D20S19, has been localized adjacent to D20S20 and D20S24 and is tightly linked to the three brain-specific phenotypes benign familial neonatal convulsions (BFNC) [15,16], low-voltage EEG (LVEEG) [17] and autosomal dominant nocturnal frontal lobe epilepsy (ADNFLE) [18]. ADNFLE is a partial epilepsy which typically begins in childhood and leads to clusters of brief seizures during light sleep or drowsing [19].…”
Section: Introductionmentioning
confidence: 99%
“…Linkage has now been established for some of the generalized human epileptic syndromes. In benign familial nenonatal convulsions (BFNCs), the EBNl and EBN2 genes have been mapped to chromosomes 20q and 8q (3)(4)(5). Linkage was reported for EPMR (Northern epilepsy syndrome) on chromosome 8p (6), and the gene (EPM1) for Unverricht-Lundborg disease has been localized to chromosome 21q (7).…”
mentioning
confidence: 99%
“…BFNE was originally mapped to the KCNQ2 locus in 1989 (Leppert et al) by linkage analysis of a large, four-generation pedigree. Further families were reported that confirmed the chromosome 20q localisation (Ryan et al, 1991;Malafosse et al, 1992). KCNQ2 was identified as the BFNE gene at this locus when a submicroscopic deletion containing KCNQ2 was detected in a single BFNE family.…”
mentioning
confidence: 84%